New Eclipidrilus species (Annelida, Clitellata, Lumbriculidae) from southeastern North America - Fend, Steven; Lenat, David R. (Zootaxa, 2012)
Three new species of Lumbriculidae from southeastern North America are attributed to Eclipidrilus Eisen. All are small worms (diameter 0.2–0.5 mm), having semi-prosoporous male ducts with the atria in X, and spermathecae in IX. Eclipidrilus breviatriatus n. sp. and E. microthecus n. sp. have crosshatched atrial musculature, similar to some E. (Eclipidrilus) species, but they differ from congeners in having small, compact spermathecal ampullae. Eclipidrilus macphersonae n. sp. has a single, median atrium and spermatheca. The new species have been collected only in Sandhills and Middle Atlantic Coastal Plain streams of North Carolina.